The Concept of Fasad as an Ecological Crisis in Surat Ar-Rum : 41 : A Comparative Study of Tafsir Al-Azhar and Tafsir Al-Misbah - Muhammad Achsanul Fawaid (Ma'had Aly As'adiyah Sengkang, 2026)
This study examines the interpretation of Surah Ar-Rum verse 41 regarding the concept of fasad as an ecological crisis according to Hamka and M. Quraish Shihab. Using a comparative approach, it highlights how their epistemological constructions and social backgrounds shape their understandings. Hamka interprets fasad as moral and spiritual decay resulting from a weakened human-divine relationship. Conversely, Shihab views it as the tangible impact of human exploitation and environmental pollution. By analyzing textual structure, social cognition, and historical context through Van Dijk’s theory, the study finds that while both scholars utilize similar sources, they differ in methodology and nuance: Hamka’s interpretation is characterized by moral preaching, while Shihab’s is contextual and applied. These findings underscore that Quranic exegesis is not merely textual but deeply influenced by the social and ideological factors that shape ecological narratives within the interpretation.